2013
DOI: 10.1002/jmv.23757
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to cytomegalovirus, parvovirus B19 and age‐dependent differences in levels of rubella antibodies among pregnant women

Abstract: Infections caused by cytomegalovirus (CMV), parvovirus B19 (B19), and rubella can lead to serious complications in pregnant women. The aim of this study was to determine the susceptibility to CMV, B19, and rubella antibodies in pregnant women in Norway. Consecutive sera samples were collected from pregnant women in two different regions in Norway. Sera were collected from age groups; ≤19, 20-24, 25-29, 30-34, 35-39, and ≥40 years old. Of the 2,000 pregnant women tested, anti-CMV IgG was positive in 62.8% anti-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
31
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 23 publications
10
31
0
1
Order By: Relevance
“…On the other hand, comparison of our seroprevalence with those reported in other countries suggests that the seroprevalence of CMV infection in pregnant women in Durango could be placed in an intermediate position of endemicity. The 65.6% seroprevalence found in pregnant women in Durango is similar to the 62.4%-66% seroprevalences reported in pregnant women in Poland [13], Japan [14], and Norway [15], and higher than the 49% seroprevalence in white British pregnant women in the United Kingdom [16] and a 42.3% seroprevalence in pregnant women in Germany [17]. In contrast, the seroprevalence found in pregnant women in Durango is lower than the 92.6%-100% seroprevalences reported in pregnant women in Iran [18], Palestine [19], Brazil [20], Turkey [21], Nigeria [22], and Cuba [23].…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, comparison of our seroprevalence with those reported in other countries suggests that the seroprevalence of CMV infection in pregnant women in Durango could be placed in an intermediate position of endemicity. The 65.6% seroprevalence found in pregnant women in Durango is similar to the 62.4%-66% seroprevalences reported in pregnant women in Poland [13], Japan [14], and Norway [15], and higher than the 49% seroprevalence in white British pregnant women in the United Kingdom [16] and a 42.3% seroprevalence in pregnant women in Germany [17]. In contrast, the seroprevalence found in pregnant women in Durango is lower than the 92.6%-100% seroprevalences reported in pregnant women in Iran [18], Palestine [19], Brazil [20], Turkey [21], Nigeria [22], and Cuba [23].…”
Section: Discussionsupporting
confidence: 79%
“…Recent studies in other European countries reported similar data: the prevalence observed in Norway was 94.4% [23] and in England between 94.9% [24] and 97.4% [25]. In the United States, the prevalence was 91.5% [26], while in Canada the prevalence was 93.2% in Canadian-born mothers but was lower in immigrants from Northern Africa, the Middle East, China and the South Pacific [27].…”
Section: Discussionsupporting
confidence: 58%
“…Adolescent and young adults aged between 15 and 30 years were identified as a group that may require booster vaccination. Several studies showed that, by this age, the level of measles and rubella antibodies were lower than other age groups studied [11,18,22,24,26,29,30,32,36,42,84,88,91,96]. Several authors recommended that teens be re-vaccinated [24,32,36,42].…”
Section: Major Findings Of the Reviewmentioning
confidence: 95%
“…Several authors demonstrated that vaccinated individuals have lower GMT compared with those acquiring immunity through natural infection [9,10,[15][16][17]19,[24][25][26]30,34,69,96,99]. There was insufficient information provided to determine if certain vaccination programmes resulted in a lower GMT.…”
Section: Major Findings Of the Reviewmentioning
confidence: 98%